Economics and Interdisciplinary Exchange in Catholic Social Teaching and “Caritas in Veritate” - Yuengert, Andrew M. 1960- (2011)
The social sciences, and particularly economics, play an important role in business. This article reviews the account of the interdisciplinary conversation between Catholic Social Teaching and the social sciences (especially economics) over the last century, and describes Benedict XVI’s development of this account in Caritas in Veritate. Over time the popes recognized that the technical approach of economics was a barrier to fruitful collaboration between economics and Catholic Social Teaching, both because the economic approach is reductionist, and because modern social science is skeptical of comprehensive accounts of human nature. Through an appeal to charity in truth, one can deduce from Caritas in Veritate that economists, along with business and management theorists, need to take seriously the project of reflecting on and promoting true human goods in society. To love the person one must reflect on what is truly good for the person; to discover the true good of the person, one must love the person.
Keywords: Practical Wisdom; Interdisciplinary; Economics and ethics; Catholic Social Teaching; Caritas in Veritate; Benedict XVI